THE DETERMINANTS AND IMPLEMENTATION OF RISK-BASED CAPITAL ON THE FINANCIAL PERFORMANCE OF INSURANCE COMPANIES IN INDONESIA - Hery, Yaudil; Hady, Hamdy; Arsjah, Regina J. (UTSAHA: Journal of Entrepreneurship, 2023)
The insurance company is one of the pillars in supporting economic growth. In Indonesia, insurance companies are required to report their solvency ratio to the government on a regular basis. Therefore, the objective of this research is to assess the effect of retention, investment assets, leverage, technical reserves and maturity mismatch on Risk Based Capital (RBC) and financial performance of insurance companies in Indonesia. This research is a quantitative approach using panel data regression method. The population of this research is companies in the insurance industrial sector in 2014-2018. The sample used in this research was 91 insurance companies. This research used secondary data obtained from financial reports published in print media and company websites during 2014-2018. The results of this research indicate that retention and investment assets have a positive effect on risk-based capital (RBC) and the financial performance of insurance companies. While leverage has no effect on risk-based capital (RBC) or financial performance of insurance companies. On the other hand, the technical reserve variable only affects the financial performance of insurance companies but has no effect on the company’s risk-based capital. In addition, the maturity mismatch variable indicates a negative effect on risk-based capital but has no effect on the financial performance of insurance companies. Meanwhile, risk-based capital affects the financial performance of insurance in Indonesia.